Inovasi Media Pembelajaran Interaktif untuk Pengajaran Matematika di Era Digital (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study aims to explore innovations in interactive learning media for mathematics education in the digital era and to evaluate their effectiveness in enhancing students' conceptual understanding. Using a Systematic Literature Review (SLR) approach, literature sources were obtained from various academic databases, including Google Scholar, ScienceDirect, DOAJ, Scopus, and SpringerLink, focusing on publications from 2014 to 2024. The findings indicate that the most commonly used interactive learning media are digital textbooks that integrate multimedia elements, such as platforms like Wizer.me and Wordwall, which contribute to students' spatial understanding and reduce conceptual misunderstandings. The use of interactive learning media has also proven effective in improving students' understanding of mathematical concepts across various educational levels, with research demonstrating significant improvements among students using interactive technology compared to those receiving conventional instruction. However, the primary challenges in implementing interactive learning media include inadequate infrastructure, teachers' readiness to adopt new technologies, and students' limited access to digital devices. This study further highlights the crucial role of digital technology in transforming mathematics teaching approaches, particularly in facilitating the visualization of abstract mathematical concepts and providing immediate feedback. Overall, these findings underscore the significant potential of interactive learning media to enhance mathematics learning experiences while emphasizing the need for further research to address existing challenges and explore the long-term implementation of these technologies in mathematics education